The Routledge handbook of epistemic injustice - Kidd, Ian James; Medina, José; Pohlhaus, Gaile M. (Routledge handbooks in philosophy, 2017)
In the era of information and communication, issues of misinformation and miscommunication are more pressing than ever. Epistemic injustice--one of the most important and ground-breaking subjects to have emerged in philosophy in recent years--refers to those forms of unfair treatment that relate to issues of knowledge, understanding, and participation in communicative practices. The Routledge Handbook of Epistemic Injustice is an outstanding reference source to the key topics, problems, and debates in this exciting subject. The first collection of its kind, it comprises over thirty chapters by a team of international contributors, divided into five parts: Core Concepts; Liberatory Epistemologies and Axes of Oppression; Schools of Thought and Subfields within Epistemology; Socio-political, Ethical, and Psychological Dimensions of Knowing; Case Studies of Epistemic Injustice. As well as fundamental topics such as testimonial and hermeneutic injustice and epistemic trust the Handbook includes chapters on important issues such as social and virtue epistemology, objectivity and objectification, implicit bias, and gender and race. Also included are chapters on areas in applied ethics and philosophy, such as law, education, and healthcare. The Routledge Handbook of Epistemic Injustice is essential reading for students and researchers in ethics, epistemology, political philosophy, feminist theory, and philosophy of race. It will also be very useful for those in related fields, such as cultural studies, sociology, education, and law.
Keywords: approches et analyses; capacitisme; cours; cycles supérieurs; discipline; fem9000; hétérosexisme; injustices épistémiques; intersectionnalité; outils; ouvrages de références; philosophie; racisme; santé; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; épistémologie; éthique; études critiques de la race; études critiques du handicap

The color of violence: The incite! anthology - INCITE! Women of Color Against Violence (Duke University Press, 2016)
The editors and contributors to Color of Violence ask: What would it take to end violence against women of color? Presenting the fierce and vital writing of organizers, lawyers, scholars, poets, and policy makers, Color of Violence radically repositions the antiviolence movement by putting women of color at its center. The contributors shift the focus from domestic violence and sexual assault and map innovative strategies of movement building and resistance used by women of color around the world. The volume's thirty pieces—which include poems, short essays, position papers, letters, and personal reflections—cover violence against women of color in its myriad forms, manifestations, and settings, while identifying the links between gender, militarism, reproductive and economic violence, prisons and policing, colonialism, and war. At a time of heightened state surveillance and repression of people of color, Color of Violence is an essential intervention.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; droits des femmes*; femmes* autochtones; femmes* de couleur; femmes* immigrantes; hétérosexisme; intersectionnalité; justice reproductive; justice sociale; militance; outils; ouvrages de références; périodes historiques; racisme; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

Geographies of privilege - Twine, France Winddance; Gardener, Bradley (Routledge, 2013)
How are social inequalities experienced, reproduced and challenged in local, global and transnational spaces? What role does the control of space play in distribution of crucial resources and forms of capital (housing, education, pleasure, leisure, social relationships)? The case studies in Geographies of Privilege demonstrate how power operates and is activated within local, national, and global networks. Twine and Gardener have put together a collection that analyzes how the centrality of spaces (domestic, institutional, leisure, educational) are central to the production, maintenance and transformation of inequalities. The collected readings show how power--in the form of economic, social, symbolic, and cultural capital--is employed and experienced. The volume's contributors take the reader to diverse sites, including brothels, blues clubs, dance clubs, elite schools, detention centers, advocacy organizations, and public sidewalks in Canada, Italy, Spain, United Arab Emirates, Mozambique, South Africa, and the United States. Geographies of Privilege is the perfect teaching tool for courses on social problems, race, class and gender in Geography, Sociology and Anthropology.
Keywords: afrique; afrique du sud; amériques; anthropologie; approches et analyses; canada; classe sociale; discipline; environnement; espagne; europe; géographie; italie; mozambique; outils; ouvrages de références; privilèges; racisme; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; émirats arabes unis; états-unis

Sovereign erotics: A collection of Two-Spirit literature - Driskill, Qwo-Li; Justice, Daniel Heath; Miranda, Deborah; Tatonetti, Lisa (The University of Arizona Press, 2011)
Les personnes bispirituelles, identifiées par de nombreux noms et positions tribales spécifiques au sein de leurs communautés, vivent, aiment et créent de l'art depuis des temps immémoriaux. Ce n’est cependant que dans les années 1970 que la littérature autochtone queer contemporaine a attiré l’attention du public. Même aujourd’hui, seule une poignée de livres en parlent spécifiquement, notamment la collection de 1988 Living the Spirit: A Gay American Indian Anthology. Depuis la publication de ce livre il y a vingt-trois ans, aucune autre collection n'a été publiée se concentrant explicitement sur l'écriture et l'art des peuples autochtones bispirituels et queer. Cette collection historique s'efforce de refléter la complexité des identités au sein des communautés autochtones gaies, lesbiennes, bisexuelles, transgenres, queer et bispirituelles (GLBTQ2). Rassemblant le travail d'écrivains confirmés et de nouvelles voix talentueuses, cette anthologie couvre les genres (fiction, non-fiction, poésie et essai) et les thèmes (mémoire, histoire, sexualité, indigénéité, amitié, famille, amour et perte) et représente un tournant décisif. moment dans les littératures amérindiennes et autochtones, les études queer et les intersections entre les deux. En collaboration, les pièces de Sovereign Erotics démontrent non seulement la diversité radicale des voix des écrivains autochtones GLBTQ2 d'aujourd'hui, mais également la beauté, la force et la résilience des personnes autochtones GLBTQ2 au XXIe siècle. Contributeurs : Indira Allegra, Louise Esme Cruz, Paula Gunn Allen, Qwo-Li Driskill, Laura Furlan, Janice Gould, Carrie House, Daniel Heath Justice, Maurice Kenny, Michael Koby, M. Carmen Lane, Jaynie Lara, Chip Livingston, Luna Maia , Janet McAdams, Deborah Miranda, Daniel David Moses, DM O'Brien, Malea Powell, Cheryl Savageau, Kim Shuck, Sarah Tsigeyu Sharp, James Thomas Stevens, Dan Taulapapa McMullin, William Raymond Taylor, Joel Waters et Craig Womack
Keywords: amérique du nord; amériques; approches et analyses; arts; discipline; discours dominant; féminisme autochtone; identités LGBTQIA2+; outils; ouvrages de références; queer; racisme; régions géographiques; système colonial; systèmes d'oppressions; études littéraires